Innovation Capability, Absorptive Capacity and SMEs Performance in Pakistan: The Moderating Effect of Business Strategy - Arshad, Muhammad Zulqarnain; Arshad, Darwina (UUM Press, 2018)
The small and medium-sized enterprises (SMEs) play a crucial part in country's economic growth and a key contributor in country's GDP. In Pakistan SMEs hold about 90 percent of the total businesses. The performance of SMEs depends upon many factors. The main aim for the research is to examine the relationship between Innovation Capability, Absorptive Capacity and Performance of SMEs in Pakistan. This conceptual paper also extends to the vague revelation on Business Strategy in which act as a moderator between Innovation Capability, Absorptive Capacity and SMEs Performance. Conclusively, this study proposes a new research directions and hypotheses development to examine the relationship among the variables in Pakistan's SMEs context.